The Neural Correlates of Creativity and Innovation in Various Domains and Contexts in Germany - Lina, Alice (International Journal of Psychology, 2024)
Purpose: The aim of the study was to investigate the neural correlates of creativity and innovation in various domains and contexts. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: Neuroscientific studies reveal that creativity and innovation engage diverse brain networks, including those governing divergent thinking and cognitive flexibility. These processes show consistent neural activation patterns across different domains, suggesting a universal basis for creativity regardless of context. Environmental factors, like novelty exposure and social interactions, also play significant roles in shaping neural activity underlying creative thinking. Unique Contribution to Theory, Practice and Policy: Conceptual blending theory, network theory of creativity & four-stage model of creativity may be used to anchor future studies on the neural correlates of creativity and innovation in various domains and contexts. Practical implications of understanding the neural correlates of creativity and innovation can inform the design of interventions and training programs aimed at fostering creative thinking skills. Policymakers can leverage insights from research on the neural correlates of creativity to inform decision-making processes related to education, workforce development, and innovation policy.